2015
DOI: 10.1039/c4an02364a
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage in DNA bases revealed by UV resonant Raman spectroscopy

Abstract: We report on the use of the UV Raman technique to monitor the oxidative damage of deoxynucleotide triphosphates (dATP, dGTP, dCTP and dTTP) and DNA (plasmid vector) solutions. Nucleotide and DNA aqueous solutions were exposed to hydrogen peroxide (H2O2) and iron containing carbon nanotubes (CNTs) to produce Fenton's reaction and induce oxidative damage. UV Raman spectroscopy is shown to be maximally efficient to reveal changes in the nitrogenous bases during the oxidative mechanisms occurring on these molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 38 publications
5
61
0
Order By: Relevance
“…As previously mentioned in describing the spectral Zone I (Figure c,d), spectral Zone II contains a clear fingerprint of a process of depletion in adenosine triphosphate due to hydrolysis of phosphoanhydride phosphate bonds that the cells employ in response to virus inoculation. In spectral Zone II after virus inoculation, the intensity of the main band of deoxyadenosine triphosphate (i.e., Band 52 at 1331 cm −1 in Table and Figures c,d; D'Amico et al, ) showed a significant reduction at 48 hr and then remained stable at the same level at 72 hr after inoculation. Concurrently, Band 33 ++ at 1090 cm −1 appeared, which arises from O–P–O stretching in adenosine diphosphate (Jenkins, Tuma, Juuti, Bamford, & Thomas, ).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…As previously mentioned in describing the spectral Zone I (Figure c,d), spectral Zone II contains a clear fingerprint of a process of depletion in adenosine triphosphate due to hydrolysis of phosphoanhydride phosphate bonds that the cells employ in response to virus inoculation. In spectral Zone II after virus inoculation, the intensity of the main band of deoxyadenosine triphosphate (i.e., Band 52 at 1331 cm −1 in Table and Figures c,d; D'Amico et al, ) showed a significant reduction at 48 hr and then remained stable at the same level at 72 hr after inoculation. Concurrently, Band 33 ++ at 1090 cm −1 appeared, which arises from O–P–O stretching in adenosine diphosphate (Jenkins, Tuma, Juuti, Bamford, & Thomas, ).…”
Section: Resultsmentioning
confidence: 93%
“…Regarding the above item (a), such newly observed emission has also been related to ring vibrations in tyrosine and it was shown strongly enhanced in oxidized deoxyguanosine triphosphate (D'Amico et al, ; Lakshimi et al, ; Thomas, ). This interpretation is supported by the observed intensity enhancement for Bands 42 and 45, which was discussed in the previous section as a fingerprint of tyrosine kinase activation upon virus inoculation (Eierhoff et al, ; cf.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The results presented in these works suggest that guanine (G) is oxidized to 8-oxoguanine Raman bands assignments of G, 8-oxoG and 8-oxoG ox have been experimentally and theoretically (DFT) proposed. 43,44,49,50 Potential dependent SERS spectra of guanine adsorbed on AuNPs/SWCNT electrode, shown in Fig. 4, and vibrational assignment, summarized in Table 2, are completely correlated to the guanine oxidation mechanism.…”
Section: Guanine Oxidationmentioning
confidence: 99%
“…Adenine oxidation mechanism has been described in previous works 21,37,38 . These works suggest that adenine (A) is oxidized to 2-oxoadenine Experimental and theoretical assignments of A, 2-oxoA and 2,8-dioxoA Raman bands has been proposed previously [39][40][41][42][43][44] from data experimentally obtained and from calculated data using density functional theory (DFT). The potential dependent SERS spectra of adenine adsorbed on AuNPs/SWCNT electrode, shown in Fig.…”
Section: Adenine Oxidationmentioning
confidence: 99%